Loquat, production and market - Caballero P.; Fernández M.A. (First international symposium on loquat, 2003)
The current state of the production and marketing of loquat in the world is described. China stands out as the main producer and Spain as the prime exporter. An important growth in the export of this fruit world-wide seems unlikely as it requires demanding distribution conditions, and large disbursements must be made for fruits to achieve commercial quality. Price analysis in Spain indicates that loquat is the horticultural fruit with the least loss of real income over the last 20 years. The difference between prices and costs indicates that acceptable profit margins exist for the grower and the price risk is low. However, the subjective risk that farmers perceive seems high due to the large investments that must be made to cope with labour costs. This prevents the possible expansion of loquat production.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)